Assessing Supermarket Food Shopper Reaction to Horsemeat Scandal in the UK - Yamoah, Fred Amofa; Yawson, David Eshun (International Review of Management and Marketing, 2014)
Consumer reaction to food scares has been given considerable research attention but insights into specific shopper segments’ reactions to food scares, especially those that do not pose direct health risk to the public is limited. This paper examines how different life-stage shopper segments reacted to the horsemeat scandal in the UK. This paper draws on the analysis of supermarket loyalty card dataset of 1.7 million beef burger shoppers to establish the effect of the horsemeat scandal on retail sales value and volume as well as the rate of withdrawal of life-stage shopper segments from the affected products. The results show consistent weekly decline in retail sales value and volume across all life-stage segments over six consecutive weeks after the first horsemeat scandal announcement. Young families, pensioners and young adults segments withdrew from affected products in accordance with their typical perception and attitudes to risk. Contrary to expectation older adults withdrew faster than young families from the affected products. The findings of the study offer useful insights and strategic direction for managers working to ensure that food scares are managed to the benefit of the public and the food industry. Keywords: Horsemeat food scare; perception and attitude to risk; life-stage shopper segments; shopper behaviour; food safety management. JEL Classification: M31